Pembangunan Sistem Informasi Manajemen Front Office Pada Graha Prima Hotel Pacitan - Taufik Hidayat Program Studi Teknik Informatika, Universitas Surakarta (SPEED - Sentra Penelitian Engineering dan Edukasi, 2017)
Abstract: Administrative data collection on the hospitality front office requires the precision of themechanism and regulation are organized so that data can be packed and properly gated.Graha Prima Hotel as one of the modern hotel in the town of Pacitan, the hotel is beingdeveloped. Currently, the existing system of rent at Graha Prima Hotel is less effective, done by way ofrecording the reservation book, late to find an empty room, preparing reports that are often late, and thecalculation of the cost of the old check out. Therefore it is to make effective in that regard, the author aimsto produce a front office information system, an efficient and effective. So the benefit that was obtainedwith a computerized system is expected to provide convenience to the front office to process customerdata in the check in and check out, providing easy storage of customer data, view reports customers,earnings reports, daily reports, monthly.With research methods the authors analyzed existing data sources for manufacturing systems, designinput and output according to analysis done, create a form - the form and code the program so that adesired system.Key Word : Front Office Management Information System at Graha Prima Hotel Pacitan